Estudo retrospectivo da anemia infecciosa equina no estado da Paraíba, Brasil, 2010-2018 - Barbosa, Gabriela Soares (2020)
Equine Infectious Anemia (EIA) is an infectious disease of worldwide distribution which affects equines in general and is caused by the Equine Infectious Anemia virus (EIAv), which belongs to the Retroviridae family and lentivirus genus. It is considered a relevant disease in equine health and must be notified in Brazil. The objective of this study was to carry out a retrospective study on equine infectious anemia in equines in the state of Paraíba from 2010 to 2018, characterize the epidemiological situation of EIA, estimate the frequency of the disease, and its distribution in the state. Data referring to positive diagnoses for EIA, notified by veterinarians qualified to perform the norms in the National Equine Health Program (PNSE), were provided by the official veterinary service. From 2010 to 2018, 694 foci of EIA were identified, distributed throughout the state. Two thousand, eight hundred and thirty-nine (2.839) horses were examined, of which 1005 animals, distributed in 104(46.6%) municipalities of Paraíba, showed positive tests for EIA. As to the species, 89%were horses, 6.7% were mules, and 4.3% were donkeys. Infectious equine anemia is present in all mesoregions of the state of Paraíba, with case reports occurring in all ofthe years of the period studied.